2015
DOI: 10.1186/s40101-015-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in physical activity and walking of healthy older adults

Abstract: BackgroundAn increasing number of older adults require improvements in their quality of life. Physical activities, particularly walking ability, are of primary importance for older adults. The influence of season on physical activity has not been sufficiently studied among older adults. Therefore, this report compared the physical activity and walking of older individuals between summer and winter seasons using a longitudinal study design in a community in a mid-latitude area.MethodsParticipants in the study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 22 publications
2
46
1
1
Order By: Relevance
“…A manutenção da atividade física, particulamente da caminhada (marcha), é crucial para uma vida independente em adultos mais velhos. 17 A caminhada é uma atividade física que pode ser praticada sem custos e que pode ser realizada em qualquer lugar, seja nas ruas, nos parques, na praia, no campo, em pistas atléticas, ginásios ou em área interna de condomínios, ou seja, qualquer lugar é adequado para uma boa caminhada, inclusive próximo as ATIs, que ficam localizadas geralmente em parques, praças e em Unidades básicas de Saúde (UBS).…”
Section: Resultsunclassified
“…A manutenção da atividade física, particulamente da caminhada (marcha), é crucial para uma vida independente em adultos mais velhos. 17 A caminhada é uma atividade física que pode ser praticada sem custos e que pode ser realizada em qualquer lugar, seja nas ruas, nos parques, na praia, no campo, em pistas atléticas, ginásios ou em área interna de condomínios, ou seja, qualquer lugar é adequado para uma boa caminhada, inclusive próximo as ATIs, que ficam localizadas geralmente em parques, praças e em Unidades básicas de Saúde (UBS).…”
Section: Resultsunclassified
“…In both studies, participants indicated the importance of the social benefits of exercise and suggested that easy access to programming-either through programs offered where people live, or by providing transportation to activities and classes-would help facilitate increased PA participation (Belza et al, 2004;Mathews et al, 2010). In these and other studies (Chan & Ryan, 2009;Clemes, Hamilton, & Griffiths, 2011;Guerin, et al, 2008;Kimura, Kobayashi, Nakayama, & Kakihana, 2015;Marquez et al, 2014), researchers have found that barriers to PA participation included personal (health/safety concerns) and environmental (lack of access and poor weather) factors.…”
Section: Introductionmentioning
confidence: 83%
“…However, one limitation of the existing research is that there were no longitudinal studies to see if the activity levels of older adults living in residential facilities was maintained throughout the year. In many parts of the world, the change of seasons may result in temperature extremes or high precipitation, factors which have been noted as barriers to older adults' ability to stay active (Aoyagi & Shephard, 2010;Kimura et al, 2015;Togo et al, 2008). Studies looking at the impact of seasonality on PA participation show mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a healthy population, there was a 2.9% decrease in steps per day for every 10 • C drop in temperature [37]. In addition to temperature, day length and daylight hours account for 73% of the monthly differences in daily activity level, and these three parameters are independent predictors of daily activities [38]. To analyze the climate conditions affecting PA in our study, we conducted a subgroup analysis to identify the relationship between climate conditions and activity for 85 people living in the capital city of South Korea.…”
Section: Discussionmentioning
confidence: 99%